2008
DOI: 10.1149/1.2800562
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Processed Indium-Zinc Oxide Transparent Thin-Film Transistors

Abstract: Transparent thin-film transistors ͑TTFTs͒ with an indium-zinc oxide ͑IZO͒ active layer by the solution-processed deposition method were fabricated and their TFT characterization was examined. Solution-processed IZO thin films were amorphous and highly transparent with Ͼ90% transmittance in the visible region with an optical bandgap of 3.1 eV. Spin-coated IZO TTFTs were operated in depletion mode and showed a field-effect mobility as high as 7.3 cm 2 /V s, a threshold voltage of 2.5 V, an on/off current ratio g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
105
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 29 publications
5
105
0
Order By: Relevance
“…An aqueous route allows for the preparation of IZO TFTs at a lower temperature compared with that used in the previously reported 2-methoxyethanol-based approach. [10][11][12] To investigate the uniformity of the devices, 36 TFTs with an IO active layer prepared via the aqueous route were fabricated at an The storage stability of a precursor solution is an important issue in sol-gel chemistry. The TFTs fabricated from pristine and 100-day-old aqueous solutions were compared with investigate the storage stability of the aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An aqueous route allows for the preparation of IZO TFTs at a lower temperature compared with that used in the previously reported 2-methoxyethanol-based approach. [10][11][12] To investigate the uniformity of the devices, 36 TFTs with an IO active layer prepared via the aqueous route were fabricated at an The storage stability of a precursor solution is an important issue in sol-gel chemistry. The TFTs fabricated from pristine and 100-day-old aqueous solutions were compared with investigate the storage stability of the aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…The high annealing temperature, which is usually 4400 1C, is not compatible with flexible plastic substrates, with conventional glass or with the stacked multi-layer structures because of the mismatch in the coefficient of thermal expansion between the layers during deposition. [10][11][12] A few studies on low-temperatureprocessable MOSs have been reported. [13][14][15][16] However, the authors of these studies used either complex and unstable precursors that required significant effort and multiple steps for synthesis or complicated chemical reactions that are not appropriate for the general fabrication technique.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports of high-performance TFTs with oxide semiconductors, including ZnO, [8][9][10] InZnO, [11][12][13] ZnSnO, [14] and InGaZnO [15][16][17][18][19] as the channel materials. The field-effect mobilities (m FE ), sub-threshold gate swing (S), and I on/ off ratios of ZnO-based TFTs have been dramatically improved since Hosono and coworkers reported the usage of amorphous InGaZnO as a channel material using physical-vapor-deposition techniques.…”
mentioning
confidence: 99%
“…A precursor solution of Zn(CH 3 COO) 2 ·2H 2 O with limited solubility in alcohols is easily precipitated or gelled, while In(CH 3 COO) 3 is not soluble in 2-ME. Both 0.4 M of Diethanolamine (DEA) and 0.4 M of acetylacetone were utilized to stabilize the IZO precursor solution (18,19). The channel width and length of all a-IGZO TFTs were 500 μm and 50 μm, respectively.…”
Section: Methodsmentioning
confidence: 99%